Microbiome affects egg carotenoid investment, nestling development and adult oxidative costs of reproduction in Great tits - Jacob, Staffan; Parthuisot, Nathalie; Vallat, Armelle; Ramon-Portugal, Felipe; Helfenstein, Fabrice; Heeb, Philipp (My University, 2015)
Parasites influence allocation trade-offs between reproduction and self-maintenance and consequently shape host life-history traits. The host microbiome includes pathogenic and commensal micro-organisms that are remarkable in their diversity and ubiquity. However, experimental studies investigating whether the microbiome shapes host reproduction are still lacking. In this study, we tested whether the microbiome affects three important components of bird reproduction, namely (i) the maternal transfer of anti-microbial compounds to the eggs, (ii) the development of nestlings and (iii) the trade-off between reproduction and self-maintenance, here measured by the oxidative costs of reproduction. We experimentally modified the microbiome of wild breeding Great tits (Parus major) by spraying nests with liquid solution that either favoured or inhibited bacterial growth compared to a control. These treatments modified the bacterial communities in the nests and on adult feathers. We found that females from the treatment that decreased bacterial densities in the nests laid eggs with less carotenoids than females from the control, while we found no significant effect of increasing bacterial densities and modifying community composition compared to the control. Nestlings exposed to decreased bacterial densities grew faster and had longer tarsus length at fledging. Moreover, our analyses revealed that the relationship between investment in reproduction and oxidative damage was affected by the treatments. Adults raising larger clutches suffered higher oxidative damage in control nests, whereas this oxidative cost of reproduction was not detected when we modified bird microbiome. Our study provides experimental evidence for an effect of the microbiome on egg carotenoid investment, nestling development and oxidative cost of reproduction and thus highlights the major effect that the microbiome may have on the evolution of host life-history strategies.
Keywords: life-history traits; maternal effects; microbial communities; nestling growth; oxidative stress